Jaminan Keselamatan Dalam Injil Yohanes 10:28-29 Dan Implikasinya Bagi Pengajar Pendidikan Agama Kristen - Zega, Yunardi Kristian (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2021)
The doctrine of salvation (soteriology) is one of the most important doctrines in Christianity. The doctrine of soteriology needs to be understood and understood properly and correctly, so as not to lead to misleading interpretations. One of the interesting verses to discuss in the doctrine of soteriology is the assurance of salvation in the Gospel of John 10: 28-29. For this reason, in this article, the author will analyze the Gospel of John 10: 28-29 in order to provide a soteriological understanding that is in accordance with the truths contained in the text. The result of the analysis of this article is that Jesus guarantees the salvation of believers so that they do not perish forever, and God the Father also guarantees this salvation. Therefore, believers will receive the power of the Holy Spirit so that they can practice every truth that God wants in their lives. Thus, every believer can have a correct understanding of the assurance of his safety. This needs to be a concern for Christian educators, whether they teach in families, schools, or churches. Doktrin keselamatan (soteriologi) adalah salah satu doktrin yang sangat penting di dalam Kekristenan. Doktrin soteriologi perlu untuk dapat dimengerti dan dipahami dengan baik dan benar, agar tidak menimbulkan penafsiran yang menyesatkan. Salah satu ayat yang cukup menarik untuk dibahas dalam doktrin soteriologi adalah mengenai jaminan keselamatan dalam Injil Yohanes 10:28-29. Untuk itu, dalam artikel ini, penulis akan menganalisis Injil Yohanes 10:28-29 agar dapat memberikan pemahaman soteriologi yang sesuai dengan kebenaran yang ada di dalam nats tersebut. Hasil dari analisis artikel ini ialah, Yesus memberikan jaminan keselamatan bagi orang-orang percaya agar tidak binasa sampai selama-lamanya, dan Allah Bapa juga ikut menjamin keselamatan tersebut. Oleh sebab itu, orang-orang percaya akan menerima kuasa Roh Kudus sehingga mereka dapat melakukan setiap kebenaran yang dikehendaki Allah di dalam kehidupannya. Dengan demikian, agar setiap orang percaya dapat memiliki pemahaman yang benar mengenai jaminan keselamatannya. Hal ini perlu menjadi perhatian bagi para pendidik Kristen, baik yang mengajar di keluarga, sekolah, maupun gereja.